How Coffee Beverage Quality Drives Consumer Satisfaction: A Quantitative Study in Bandung - Ismail, Hariadi (Business Journal : Jurnal Bisnis Dan Sosial, 2025)
This study examines the influence of coffee beverage product quality on consumer satisfaction at Yellow Truck Coffee Bandung. Using a quantitative approach with multiple regression analysis, the research evaluates four dimensions of product quality. The findings suggest that visual appeal and presentation play a key role in shaping consumer perceptions. Managerially, Yellow Truck Coffee Bandung is advised to expand and refine its coffee menu variants, enhance barista responsiveness and service speed, and implement a guest comment system to better capture customer feedback. Strengthening these areas is expected to improve overall consumer satisfaction and support the coffee shop’s competitive performance.